The Politics of Whiteness: Race, Workers, and Culture in the Modern South - McCartin, Joseph A. (Labour / Le Travail, 2004)
The article reviews the book, "The Politics of Whiteness: Race, Workers, and Culture in the Modern South," by Michelle Brattain.